2023
DOI: 10.1007/s15010-023-02125-5
|View full text |Cite
|
Sign up to set email alerts
|

Early combination therapy of COVID-19 in high-risk patients

Hans Martin Orth,
Charlotte Flasshove,
Moritz Berger
et al.

Abstract: Purpose Prolonged shedding of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been observed in immunocompromised hosts. Early monotherapy with direct-acting antivirals or monoclonal antibodies, as recommended by the international guidelines, does not prevent this with certainty. Dual therapies may therefore have a synergistic effect. Methods This retrospective, multicentre study compared treatment strategies for corona virus disease-19 (CO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…18 In vivo data also demonstrated prolonged viral clearance in patients with severe immunocompromise, including the hematooncology population. 19 Prolonged positivity in SOT recipients is less frequently described; however, it is unclear whether this represents a lower burden of prolonged positivity in this population or publication bias. Some multicentre studies have demonstrated higher numbers of SOT recipients than those with haematologic malignancies, but this may reflect the underlying patient populations seen at these institutions.…”
Section: Prolonged Sars-cov-2 Test Positivitymentioning
confidence: 94%
“…18 In vivo data also demonstrated prolonged viral clearance in patients with severe immunocompromise, including the hematooncology population. 19 Prolonged positivity in SOT recipients is less frequently described; however, it is unclear whether this represents a lower burden of prolonged positivity in this population or publication bias. Some multicentre studies have demonstrated higher numbers of SOT recipients than those with haematologic malignancies, but this may reflect the underlying patient populations seen at these institutions.…”
Section: Prolonged Sars-cov-2 Test Positivitymentioning
confidence: 94%